English in paradise: the Maldives: English is rapidly establishing itself as a second language in a society transforming from fishing to tourism and trade. Issue 1 (10th December 2017) - Meierkord, Christiane
Abstract : The spread of English has reached almost every corner of the world, and the Republic of the Maldives is no exception. Following the nation's opening to the outside world, the introduction of English as a medium of instruction at secondary and tertiary level of education, and its government's recognition of the opportunities offered through tourism, English has now firmly established itself in the country. As such, Maldives is quite similar to the countries in the Gulf region (cf. Randall & Samimi, 2010; Boyle, 2012). The nation is undergoing vast societal change, and English is part of this.